Fitness & Sports Medicine - Lechner K; Lechner B; Engel H; Halle M; Worm N; Scherr J (Dynamic Media Sales Verlag, 2020)
Vitamin D (VitD) and its physiological function in regulating calcium/phosphorus absorption and bone remineralization werefirst described in the early 20thcentury. A better understanding of VitD signaling has advanced our understanding of the importance of adequate VitD status to human health and performance. Tissues relevant to athletes which depend on VitD for optimal function include innate and adaptive immune system, skeletal muscle, and bone. Cross-sectional studies have shown that more than half of athletes are deficient and/or insufficient in VitD. Correcting insufficiency, the suggested target of25(OH)D blood levels above 30 ng/ml has the potential to optimize various aspects related to performance and regeneration in VitD insufficient athletes. This might help athletes to reach their full potential. Of note, there is no evidence pointing to actual or potential health risks of VitD levels within the recommended limits. VitD is therefore not on the list of prohibited substances of the world anti-doping agency.To avoid toxicity, VitD status should be monitored and supplementation strategies should be individualized and target-oriented. In terms of effectiveness and safety, low-dosed, continuous supplementation strategies of VitD are superior to intermittent application of supraphysiological boluses. The concept of synergy between nutrients lends qualified support tothe assumption that VitD bioavailability and function depend on meal context and onthefat-soluble vitamins A and K2 as well as the minerals magnesium and zinc. KEY WORDS: Regeneration, Immune System, Muscular Function, Bone Health, Supplementation Strategies